Miracle on 34th Street [videorecording (DVD)] - Seaton, George, 1911-1979; Perlberg, William, 1899-1969; Davies, Valentine, 1905-1961; O'Hara, Maureen, 1920-2015; Payne, John, 1912-1989; Gwenn, Edmund, 1875-1959; Lockhart, Gene, 1891-1957; Wood, Natalie; Hall, Porter, 1888-1953; Frawley, William, 1887-1966; Cowan, Jerome, 1897-1972; Tonge, Philip, 1897-1959; et al. (Twentieth Century Fox Home Entertainment, 2012)
1947: The real Santa is hired by Macy's to play the department store's Santa in the Thanksgiving Day parade, but has to prove in court that he is who he says he is.